Valuation Risk and Asset Pricing. (December 2016) - ALBUQUERQUE, RUI; EICHENBAUM, MARTIN; LUO, VICTOR XI; REBELO, SERGIO
ABSTRACT: Standard representative‐agent models fail to account for the weak correlation between stock returns and measurable fundamentals, such as consumption and output growth. This failing, which underlies virtually all modern asset pricing puzzles, arises because these models load all uncertainty onto the supply side of the economy. We propose a simple theory of asset pricing in which demand shocks play a central role. These shocks give rise to valuation risk that allows the model to account for key asset pricing moments, such as the equity premium, the bond term premium, and the weak correlation between stock returns and fundamentals.